2015
DOI: 10.1055/s-0035-1557831
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological, Antidiarrheal and Spasmolytic Activities of Solanum paniculatum

Abstract: Solanum paniculatum is popularly known as "jurubeba-verdadeira". In folk medicine, its roots, stems, and leaves are used as tonics, anti-inflammatories, carminatives, diuretics, and for gastrointestinal disorders. This species is listed in the Brazilian Pharmacopoeia and belongs to the "Relação Nacional de Plantas Medicinais de Interesse ao SUS". Based on folk medicine data of the Solanum genus, we decided to investigate whether the crude ethanol extract from S. paniculatum aerial parts presents toxicological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Solanum paniculatum L., popularly known in Brazil as jurubeba, is a native plant species from South America with several uses in the culinary area and folk medicine. 1 Studies of the benefits of jurubeba have been compiled by European naturalists since the 19th century, including the famous German botanist C. F. P. von Martius. 2 Preparations using roots and stems are indicated for the treatment of liver and digestive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Solanum paniculatum L., popularly known in Brazil as jurubeba, is a native plant species from South America with several uses in the culinary area and folk medicine. 1 Studies of the benefits of jurubeba have been compiled by European naturalists since the 19th century, including the famous German botanist C. F. P. von Martius. 2 Preparations using roots and stems are indicated for the treatment of liver and digestive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Baseado no fato de que diversas espécies de Solanum já apresentaram atividade espasmolítica sobre o músculo liso (OLIVEIRA et al, 2006a,b;PARMAR;GANGWAL;SHETH, 2010;MONTEIRO et al, 2012;CORREIA, 2009;CAVALCANTE et al, 2013;CLEMENTINO-NETO et al, 2015) e que Santos et al (2003) demonstraram que o extrato obtido do caule de Solanum stipulaceum apresenta efeito espasmolítico, resolveu-se investigar se o extrato obtido das partes aéreas desta espécie também apresentaria esta atividade.…”
Section: Resultsunclassified
“…Elephant apple ( D. indica ) is a prominent species which contains chemical substances that can be applied for medicinal purposes, such as β‐sitosterol and stigmasterol for their antimicrobial activity (Dey, Mukherjee, De, & Pandey, ; Ododo, Choudhury, & Dekebo, ), as well as vitamin E for its antioxidant features (Muhit, Tareq, Apu, Basak, & Lslam, ; Yeshwante et al, ). These four components also have anti‐inflammatory (Parvin et al, ) and antidiarrheal properties (Clementino‐Neto et al, ; Singh & Gupta, ). The methanolic crude extract showed that the leaves provide a rich source of triterpenoids and flavonoids (Abreu et al, ).…”
Section: Introductionmentioning
confidence: 99%